Use of Clinical Audits to Evaluate Timing of Preoperative Antimicrobials in Equine Surgery at a Veterinary Teaching Hospital - Ceriotti, Serena; Westerfeld, Roxane; Bonilla, Alvaro G.; Pang, Daniel S. J. (Frontiers in Veterinary Science, 2021)
Based on human surgical guidelines, intravenous antimicrobials are recommended to be administered within 60 minutes of surgical incision. Achieving this target is reportedly challenging and influenced by hospital policies. Study objectives were to evaluate and improve: 1) timing of antimicrobial administration to surgical incision (tAB-INC), 2) contributions of anesthesia pre-induction (tPRI) and surgical preparation (tPREP) periods to tAB-INC, 3) completeness of antimicrobial recording. Two clinical audits were conducted before and after policy changes (patient preparation and anesthesia record keeping). tPRI, tPREP and tAB-INC were calculated and compared for elective arthroscopies and emergency laparotomies within and between audits. Percentage of procedures with a tAB-INC < 60 min was calculated. Antimicrobial recording was classified as complete or incomplete. A median tAB-INC < 60 minutes was achieved in laparotomies (audit 1; 45 minutes, audit 2; 53 minutes) with a shorter tPREP than arthroscopies (P < 0.0001, both audits). Percentage of procedures with tAB-INC < 60 minutes, tAB-INC, tPRI and tPREP durations did not improve between audits. The number of operated joints positively correlated with tPREP (audit 1, P < 0.001, r = 0.77; audit 2, P < 0.001, r = 0.59). Between audits, antimicrobial recording significantly improved for elective arthroscopies (82% to 97%, P = 0.008) but not emergency laparotomies (76% to 88%, P = 0.2). Clinical audit successfully quantified the impact of introduced changes and adherence to antimicrobial prophylaxis guidelines. Antimicrobial recording improved but further policy changes are required to achieve a tAB-INC < 60 minutes for arthroscopies.